2008
DOI: 10.1071/rd08095
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of zygote arrest 1 (ZAR1), maternal antigen that embryo requires (MATER), growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) genes in ovine oocytes and in vitro-produced preimplantation embryos

Abstract: The expression patterns of four maternal effect genes (MEG), namely zygote arrest 1 (ZAR1), maternal antigen that embryo requires (MATER), growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), were determined in ovine oocytes and in vitro-produced preimplantation embryos. The existence of ZAR1 and MATER in ovine species has not been reported previously. Reverse transcription-polymerase chain reaction was performed on germinal vesicle and IVM MII oocytes, as well as in in vitro ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…We have analysed the expression pattern of four MEGs during sheep pre-implantation development [29]. Results showed that the relative abundance of ZAR1, MATER, BMP15 and GDF9 is dynamically regulated during the window from meiotic maturation through EGA, in accordance with data in cattle [30].…”
Section: Maternal Effect Genes: Expression Patterns In Animal Modelssupporting
confidence: 62%
“…We have analysed the expression pattern of four MEGs during sheep pre-implantation development [29]. Results showed that the relative abundance of ZAR1, MATER, BMP15 and GDF9 is dynamically regulated during the window from meiotic maturation through EGA, in accordance with data in cattle [30].…”
Section: Maternal Effect Genes: Expression Patterns In Animal Modelssupporting
confidence: 62%
“…These genes, which are called maternal effect genes and which include NLRP5, Zygotic Arrest 1 (Zar1) [8,9], Stella [10,11] and Nucleoplasmin 2 (Npm2) [12], are all required for normal embryonic development beyond the 1-and 2-cell stage in mice [13,14]. Knock-out of these genes leads to incapacity of the embryo to develop beyond the 2-cell stage [15].…”
mentioning
confidence: 99%
“…The SCMC is localized in the subcortical region of mouse cleavage-stage embryos, although excluded from regions of cell-cell contact (5). The SCMC transcripts expression pattern has been previously reported in ovine oocyte and pre-implantation embryos (12,30). Our recent study on bovine oocyte showed Filia protein distribution through the cytoplasm of antral follicles (14).…”
Section: Discussionmentioning
confidence: 56%